Measurement and prediction of thermal properties of pantoa during deep-fat frying - K C, Neethu; Emerald, F Magdaline Eljeeva; Pushpadass, Heartwin A (Indian Journal of Dairy Science, 2020)
Thermal properties of pantoa were determined during deep-fat frying in sunflower oil at 125-145Â°C. Thermal conductivity (k: 0.357 to 0.199 Wm-1K-1), thermal diffusivity (Î±: 0.105x10-6 to 0.140x10-6 m2s-1) and volumetric specific heat (Cp: 3.275 to 1.401 MJm-3K-1) were measured simultaneously using dual probe heat pulse technique.Â Thermal conductivity and volumetric specific heat of pantoa decreased as the moisture content decreased, while thermal diffusivity increased with the decrease in moisture content. Empirical models were also developed as a function of moisture content, fat content and temperature of frying of pantoa. It was found that moisture content was inversely related to fat content during the progress of frying. The thermal properties and the developed models would be useful in the mathematical modeling of heat transfer in pantoa during DFF.